ELDERLY CENTER: AGE IN PLACE THROUGH LIVING WITH NATURE - Budianto, Valary
In this era, Indonesia began to experience demographic changes due to the improvement in the quality of health, technology, and sanitation. Despite the rising number of elderly population, the establishment of inclusive facility that can accommodate their lifestyle is still not in place. The scarcity of senior communities has also contributed to the lack of freedom and passive pattern of life. Not to mention, the low level of respect for the elders, inadequate health insurance, and high medical costs could then generate a feeling of helplessness that can evoke anxiety and stress, which then ends in depression. Situated on the northern edge of Bandung, this project aims to create a built environment that is able to reduce the level of depression in elderly individuals and communities, through social spaces that can prevent loneliness, spaces and activities that channel hobbies, self-actualization, as well as fulfil economic needs, and age-friendly facilities that demonstrate the beauty of life. In order to achieve this vision, the project consists of three different functions, including Congregate Housing, Elderly Community Center, and hospitality. These typologies are combined to produce a good quality of life so that the elders can live in the same place and community for as long as possible (age in place). That being said, all the facilities in the project act as supporting elements for a healthy, active, and productive lifestyle.